The аviation еngine’s gas plume model according to the american model aermod - Запорожець, О.І.; Синило, К.В. (Proceedings of National Aviation University (archive), 2004)
The examination of aviation engine’s gas plume model according to the american model Aermod was done. The plume rise’s height was determined using Aermod program algorithm. The comparison analysis of obtained results with complex model of National Aviation University was done for different regimes of aviation engine and different values of wind speed.